Interlinking securities settlement systems: a strategic commitment? - Karlo Kauko (European Central Bank (ECB), 2005)
Central securities depositories (CSDs) have opened mutual links, but most of them are seldom used. Why are idle links established? By allowing a foreign CSD to offer services through the link the domestic CSD invites competition. The domestic CSD can determine the cost efficiency of the rival by charging suitable fees, and prevent it from becoming more competitive than the domestic CSD. By inviting the competitor the domestic CSD can commit itself not to charge monopoly fees for secondary market services. This enables the domestic CSD to charge high fees in the primary market without violating investors' participation constraints.
Keywords: G29; L13; 330; access pricing; central securities depositories; network industries; securities settlement systems; Wertpapierhandel; Theorie